Cause of and countermeasures for oxidation of the cysteine‐derived reagent used in the amino acid derivative reactivity assay. Issue 2 (16th September 2018) - Fujita, Masaharu; Yamamoto, Yusuke; Watanabe, Shinichi; Sugawara, Tsunetsugu; Wakabayashi, Koji; Tahara, Yu; Horie, Nobuyuki; Fujimoto, Keiichi; Kusakari, Kei; Kurokawa, Yoshihiko; Kawakami, Tsuyoshi; Kojima, Kohichi; et al.
Abstract: The amino acid derivative reactivity assay (ADRA) is an in chemico alternative to animal testing for skin sensitization that solves certain problems found in the use of the direct peptide reactivity assay (DPRA). During a recent validation study conducted at multiple laboratories as part of the process to include ADRA in an existing OECD test guideline, one of the nucleophilic reagents used in ADRA— N ‐(2‐(1‐naphthyl)acetyl)‐l ‐cysteine (NAC)—was found to be susceptible to oxidation in much the same manner that the cysteine peptide used in DPRA was. Owing to this, we undertook a study to clarify the cause of the promotion of NAC oxidation. In general, cysteine and other chemicals that have thiol groups are known to oxidize in the presence of even minute quantities of metal ions. When metal ions were added to the ADRA reaction solution, Cu 2+ promoted NAC oxidation significantly. When 0.25 μm of EDTA was added in the presence of Cu 2+, NAC oxidation was suppressed. Based on this, we predicted that the addition of EDTA to the NAC stock solution would suppress NAC oxidation. Next, we tested 82 chemicals used in developing ADRA to determine whether EDTA affects ADRA's ability to predict sensitization. The results showed that the addition of EDTA has virtually no effect on the reactivity of NAC with a test chemical, yielding an accuracy of 87% for predictions of skin sensitization, which was roughly the same as ADRA. Abstract : The NAC of the nucleophilic reagent used in the ADRA is easily air‐oxidized, because it has an SH group. We found that the cause of this oxidation promotion was Cu 2+, and it was solved by adding trace amount of EDTA in the NAC stock solution. Furthermore, by comparison with conventional ADRA, it was revealed that addition of EDTA does not affect prediction accuracy of skin sensitization.